Tradisi Arak Manten Kucing Di Desa Sumberejo Kabupaten Malang - Ardhianto, Frandhica Wahyu; Widodo, Wahono; Istiq'faroh, Nurul (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
Through ethopedagogy, education is designed to value and integrate local knowledge, traditions, and ways of learning that are unique to the community. This research aims to explore the potential of Dermo Temple as a vehicle for ethnoscience learning at the elementary school level. Through a qualitative approach with a development research design, this study analyzes the potential of Dermo Temple in integrating science knowledge with local cultural values. Data were collected through interviews, observations, and questionnaires. The results showed that Dermo Temple has enormous potential as a learning resource rich in historical, cultural, and scientific values. The impact of this research is that there are two kalamakala statues and winged human statues found and are currently in the Trowulan museum. Candi Dermo-based learning can increase students' learning motivation, develop critical thinking skills, creativity, and problem-solving abilities, and foster a sense of love for the nation's culture and heritage. In addition, this research also highlights the importance of cooperation between schools, museums, and communities in developing sustainable learning programs. The conclusion of this research is that Dermo Temple is not only a historical site, but also a learning center that inspires the younger generation to appreciate and preserve the nation's cultural heritage.